2019
DOI: 10.2147/clep.s197251
|View full text |Cite
|
Sign up to set email alerts
|

<p>The positive predictive value of spontaneous subarachnoid hemorrhage diagnoses in the Danish National Patient Register</p>

Abstract: Introduction: Spontaneous (non-traumatic) subarachnoid hemorrhage (ntSAH) is frequently suspected in the emergency department, but the incidence rate is low. Diagnosis registers can provide valuable data for research in uncommon conditions like ntSAH. Unfortunately, validity vary in the registers. We aimed to assess the validity of the ntSAH diagnosis in the Danish National Patient Register (DNPR) and secondly to describe patients misclassified as ntSAH and to calculate the incidence rate of ntSAH. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 25 publications
0
10
1
Order By: Relevance
“…We found that the prevalence or incidences of Alzheimer's disease, Parkinson's disease, narcolepsy, and intracerebral hemorrhage were representative of the Danish and other Western populations ( Supplementary Table 7 ) ( 63 ). However, the prevalence of ischemic stroke, subarachnoid hemorrhage, and GBS were higher than previous reports from Denmark ( 64 – 66 ). While these results may be surprising, they are in line with a recent Danish study of 23,688 individuals that showed an increase in ischemic stroke in the pandemic period from March 13, 2020 – February 28, 2021, ( 67 ) and another showing increasing rates of GBS from 2019 to 2020 ( 68 ).…”
Section: Discussioncontrasting
confidence: 78%
“…We found that the prevalence or incidences of Alzheimer's disease, Parkinson's disease, narcolepsy, and intracerebral hemorrhage were representative of the Danish and other Western populations ( Supplementary Table 7 ) ( 63 ). However, the prevalence of ischemic stroke, subarachnoid hemorrhage, and GBS were higher than previous reports from Denmark ( 64 – 66 ). While these results may be surprising, they are in line with a recent Danish study of 23,688 individuals that showed an increase in ischemic stroke in the pandemic period from March 13, 2020 – February 28, 2021, ( 67 ) and another showing increasing rates of GBS from 2019 to 2020 ( 68 ).…”
Section: Discussioncontrasting
confidence: 78%
“…21,22 As the Stroke Registry did not include patients with SAH until 2017, we identified these patients from the Danish National Patient Registry, which covers all Danish hospitals. Because of the moderate positive predictive value of the SAH diagnosis (61%-67%), 23 we focused primarily on ischemic stroke and ICH.…”
Section: Study Populationmentioning
confidence: 99%
“…The uncharacteristic and diverse symptoms may result in initial under-triage and subsequent treatment delays even when patients are seen face-to-face by medical professionals in emergency departments [ 6 ]. In addition, SAH is a rare event with an incidence rate of 5.5 per 100,000 person-years [ 7 ] and consequently EMDs will infrequently encounter these patients. Our knowledge of SAH symptoms is predominantly based on retrospective studies [ 8 , 9 ] and patients’ presentations in emergency department settings [ 10 ].…”
Section: Introductionmentioning
confidence: 99%